History of the Czech Copyright Regulation - Radka MacGregor Pelikánová (Journal on European History of Law)
As with other central European countries, the Czech Republic has enjoyed a long continental legislative evolution. As a matter of fact, intellectual property and specifically Copyright is an integral part of the national law valid in the territory of the current Czech Republic for over two hundred years. During this longer period occurred many political changes with a strong legislative impact. The Copyright in the Habsburg monarchy had many similarities to the Czech Copyright between the World Wars, but just very few with the socialist legislation in the Stalinist and normalization Communist era. Fortunately, the times of the powerful leadership of the labor class is over and the current Czech Copyright satisfies the standards of the civilized and modern Europe. That being said,it is always interesting and inherently enriching to take a step back from the status quo and to reflect upon what got us to this point, to critically review the legislative evolution. The myriad of Copyright Acts valid in the territory of the Czech Republic represents a great example for a comparative overview done in a chronological manner. The ultimate result of such an overview is an increase in one’s historical awareness, as well as in the ability to understand current regulation,s and in the capacity to present legitimate comments regarding de lege lata as well as de lege ferenda.